Study on Coal Pillar Size Design Based on Non-integral Contact Structure of Coal and Rock Under Static and Dynamic Loads - Li, Qinghai; Li, Jingkai; Wang, Zhiqiang; Li, Kaixin; Zhang, Cunzhi (Frontiers in Materials, 2021)
Reasonable coal pillar size of roadway protection is an important guarantee for roadway stability under the action of static-dynamic coupling loadings in deep mines. Coal pillar and roof-floor rock form a non-integral contact structure of coal and rock. However, in the existing literature, there is no research on the size of coal pillar under static-dynamic coupling loadings based on the non-integral contact structure of coal and rock. In this study, the coal-rock non-integral contact composite specimens are designed, and the coal pillar size is simulated by the radial sizes of the specimens. The failure characteristics of coal-rock under the static-dynamic coupling loadings are studied by SHPB test, which provides the basis for the design of coal pillar size, and finally determines the reasonable coal pillar size by combining with numerical simulation. The test results show that the strength of the specimens decreases with the decrease of coal sections sizes and increases with the increase of dynamic load, but there is a critical value for static load. When the coal sections radial sizes are 50mm, 45mm and 40mm and dynamic loads are applied, the stress-strain curve of the specimens have plastic stage, but the rests do not exist. The minimum coal section radial size which can ensure the stability of the specimens is 40mm, and the similar calculation of coal pillar size is 88 m. Combined with numerical simulation, the final coal pillar size is 90 m. This study provides a more accurate and reliable method to determine the size of coal pillar under the action of static-dynamic coupling loadings.